Methodical Principles for Determination of Optimum Breaking Places of Distributive Electrical Networks with Due Account of Supply Network of 110 kV and Higher - M. I. Fursanov; A. A. Zalatoi; V. V. Makarevich; A. N. Mukha (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A specified model and algorithm for optimization of slit points in a distributive 10 (6) kV electrical network with due account of supply network of 110 kV and higher have been developed in the paper. In order to determine loss values in supply network a special mathematical model of the closed network has been constructed and the model permits to execute the given operation with minimum computing expenses. The paper proposes and analyzes methods for registration of task limitations: damage due to insufficient supply of electric power, possible network overloads for permissible currents, power supply provision for the 1st category consumers, prohibition against switching in public network and switching-on of sectional apparatus being switched-off according to normal scheme.